European Union Capitals in the Face of Smart City and Age-Friendly Challenges – Analysis and Ranking of Cities - Marek SZCZEPAŃSKI; Józef FRĄŚ (Communications of International Proceedings, 2026)
Research objective: The aim of the paper is to analyze the capitals of European Union countries in terms of implementing and improving solutions that promote a dignified life for older people, in the context of developing smart and age-friendly cities. Methodology: A comparative analysis and ranking of EU capitals were conducted, taking into account social, technological, and information and communication solutions supporting ageing societies. Main findings and their significance: The results made it possible to identify good practices and determine directions for the development of age-friendly cities. The conclusions provide important guidance for planning the development of other cities both within the European Union and globally.
Keywords: smart cities; senior-friendly destinations; capitals of EU countries; comparative analysis; ranking of capital.